Community‐level burden of acute diarrhoeal illness in the first 2 years of life in Brisbane, Australia: A birth cohort study. (3rd September 2020) - Mihala, Gabor; Grimwood, Keith; Lambert, Stephen B; Ware, Robert S
Abstract : Aim: This study sought to describe the burden of acute diarrhoeal illness (ADI) in an Australian subtropical urban setting following rotavirus vaccine introduction and to investigate the associations between child/family characteristics and ADI. Methods: Parents of 154 children from the Observational Research in Childhood Infectious Diseases birth cohort provided daily symptom and health‐care data until the age of 2 years. Results: The incidence rate of ADI was 1.07 per child‐year (95% confidence interval: 0.94–1.21). The median length of episode duration was 3 days (25th–75th percentiles: 1–6). The incidence rate was significantly higher in the first month of life and between 6 and 17 months of age compared with 18–23 months, also for children with siblings and in formal childcare. Overall, 49% of ADI episodes led to health‐care visits. Conclusions: Despite a successful rotavirus vaccine programme, ADI still results in a substantial disease burden affecting young Australian children and their families.